Reproductive behaviors among school-based health center clients in New Mexico - Perez, Mayra; Kelley, Allyson (Frontiers in Reproductive Health, 2024)
School-based health centers (SBHCs) are an evidence-based model for providing contraceptives to adolescents. SBHCs ability to provide reproductive health services is often limited by school district policies, state laws, and health center policies. We used data from the Teens Exploring and Managing Prevention (TEMPO) study to document demographic characteristics and birth control methods among patients at four SBHCs in New Mexico. A total of 264 teens were included in the baseline data collection at SBHCs in New Mexico. A baseline survey was administered via iPad, that specifically focused on questions related to sexual experiences and sexual health topics. Baseline questions included demographic questions, gender identity, sexual orientation, reasons for visits, reproductive practices, and birth control methods. Descriptive statistics were calculated, including means and standard deviations for continuous variables and categorical frequencies. Our findings present reproductive health behaviors among New Mexican patients attending schools with SBHCs. These behaviors are essential for policymakers to consider as they address policy gaps, the complex landscape of parental permission, reproductive rights, and health as a human right.School-based health centers (SBHCs) are an evidence-based model for providing contraceptives to adolescents. While SBHCs are lauded as an effective population-based strategy to support healthy sexual behaviors, their ability to provide reproductive health services is limited by school district policies, state laws, and health center policies. We used data from the Teens Exploring and Managing Prevention (TEMPO) study to document demographic characteristics and birth control methods among patients at four SBHCs in New Mexico. A total of 264 teens were included in the baseline data collection at SBHCs in New Mexico. Our findings present reproductive health behaviors among New Mexican patients attending schools with SBHCs. These behaviors are essential for policymakers and policymakers to consider as they navigate the complex landscape of parental consent, reproductive rights, and health as a human right.